Photocatalytic Degradation of Alizarin Red S, Amaranth, Congo Red, and Rhodamine B Dyes Using UV Light Modified Reactor and ZnO, TiO2, and SnO2 as Catalyst. (12th January 2021) - Rehman, Rabia; Waheed-Uz-Zaman,; Raza, Asma; Noor, Warda; Batool, Amna; Maryem, Hamna
Abstract : The photocatalytic degradation of dyes (alizarin red S, amaranth, congo red, and rhodamine B) present in wastewater was performed with UV lamp. The catalysts employed for this investigation were ZnO, TiO2, and SnO2 . The kinetic studies of dyes degradation followed first order reaction. ZnO was found to be most efficient photo-catalyst for degrading these dyes. The optimal result for alizarin red S was k = 0.2118 min −1, t 1/2 = 3.27 min, and R 2 = 0.7998, for amaranth was k = 0.146 min −1, t 1/2 = 4.74 min, and R 2 = 0.8348, for congo red was k = 0.2452 min −1, t 1/2 = 2.8 min, and R 2 = 0.8382, and for rhodamine B was k = 0.1915 min −1, t 1/2 = 3.6 min, and R 2 = 0.76.